2017
DOI: 10.15448/1980-6523.2017.1.26332
|View full text |Cite
|
Sign up to set email alerts
|

Training study of undergraduate dentistry students in a public institution of Espírito Santo face to medical urgencies/emergencies

Abstract: OBJECTIVE: This study aimed to evaluate the knowledge and confidence of undergraduate dentistry students in clinical stage about emergency situations in a public higher education institution in the state of Espírito Santo, Brazil. METHODS: This is a cross-sectional descriptive study in which a questionnaire with 12 multiple choice questions was used to evaluate the level of knowledge and confidence of dentistry students. In addition, a long answer question was used in order to describe any previous experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…[ 23 ]) found that skills in BLS, defibrillation, and airway patency showed a notable decline within 6 months of training. Other authors (Mutz and Cancado[ 24 ]) have recommended providing incentives to practitioners, who sought continued professional training in BLS, as a means to encourage active participation in BLS training courses. Notwithstanding the limitations of the present and previously published studies within the realm of medical emergencies, there is sufficient evidence to highlight the gaps in knowledge which should essentially initiate a discourse on the inclusion of a collaborative hands-on training in medical emergencies in the existing dental undergraduate curriculum on a more global scale.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ]) found that skills in BLS, defibrillation, and airway patency showed a notable decline within 6 months of training. Other authors (Mutz and Cancado[ 24 ]) have recommended providing incentives to practitioners, who sought continued professional training in BLS, as a means to encourage active participation in BLS training courses. Notwithstanding the limitations of the present and previously published studies within the realm of medical emergencies, there is sufficient evidence to highlight the gaps in knowledge which should essentially initiate a discourse on the inclusion of a collaborative hands-on training in medical emergencies in the existing dental undergraduate curriculum on a more global scale.…”
Section: Discussionmentioning
confidence: 99%